2020
DOI: 10.1038/s41467-020-18781-2
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 and interferon inflammation regulate SARS-CoV-2 entry factor expression in the airway epithelium

Abstract: Coronavirus disease 2019 (COVID-19) is caused by SARS-CoV-2, an emerging virus that utilizes host proteins ACE2 and TMPRSS2 as entry factors. Understanding the factors affecting the pattern and levels of expression of these genes is important for deeper understanding of SARS-CoV-2 tropism and pathogenesis. Here we explore the role of genetics and co-expression networks in regulating these genes in the airway, through the analysis of nasal airway transcriptome data from 695 children. We identify expression quan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
126
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 84 publications
14
126
4
Order By: Relevance
“…However, transcriptional levels still remain reduced on day 6 p.i., albeit testosterone levels already start to recover on day 6 p.i.. This observation is in line with previous reports on ACE2 and TMPRSS2 downregulation in SARS-CoV infected cells [15][16][17] . These data might suggest that the transcription of SARS-CoV-2 entry factors might not be exclusively controlled by testosterone.…”
Section: Sars-cov-2 Infection In the Lung Correlates With Reduced Acesupporting
confidence: 92%
“…However, transcriptional levels still remain reduced on day 6 p.i., albeit testosterone levels already start to recover on day 6 p.i.. This observation is in line with previous reports on ACE2 and TMPRSS2 downregulation in SARS-CoV infected cells [15][16][17] . These data might suggest that the transcription of SARS-CoV-2 entry factors might not be exclusively controlled by testosterone.…”
Section: Sars-cov-2 Infection In the Lung Correlates With Reduced Acesupporting
confidence: 92%
“…Moreover, our analysis shows that TMPRSS2 expression is not altered by interferon Accordingly, it has recently been reported that interferon inflammation does not modulate TMPRSS2 expression but upregulates ACE2 expression [12]. Instead, TMPRSS2 expression in airway epithelia is highly upregulated by IL-13 [12,14], a highly expressed cytokine in plasma of COVID-19 patients that require ventilation [13]. Furthermore, IL-13 is also involved in allergic airway type 2 inflammation, asthma and chronic obstructive pulmonary disease (COPD) [12,14], thus suggesting a further mechanism for COVID-19 susceptibility and severity.…”
Section: Analysis Of Tmprss2 Expression Datasupporting
confidence: 50%
“…This evidence suggests that concomitance with other infections, and some workplace pollutants could make lung cells more susceptible to the SARS-CoVs. Moreover, our analysis shows that TMPRSS2 expression is not altered by interferon Accordingly, it has recently been reported that interferon inflammation does not modulate TMPRSS2 expression but upregulates ACE2 expression [12]. Instead, TMPRSS2 expression in airway epithelia is highly upregulated by IL-13 [12,14], a highly expressed cytokine in plasma of COVID-19 patients that require ventilation [13].…”
Section: Analysis Of Tmprss2 Expression Datamentioning
confidence: 50%
See 2 more Smart Citations